A qualitative assessment of the role of mobile phone technology in enhancing motorcycle taxi services in Dar es Salaam, Tanzania - Nkonoki, Emma; Hamza, Vedasto (Taylor & Francis, 2025)
Motorcycle taxis (MCT) have become a popular means of mobility in Sub-Saharan Africa. Information and communication technologies (ICT) have facilitated the revolution of these services. This study assesses the role of technology in the revolution of motorcycle taxis (MCT) services in Dar es Salaam, Tanzania. The study was a qualitative case study with data collected from 35 research participants. This study found that mobile phone technology is increasingly used by MCT drivers and customers to facilitate the provision and consumption of services. The technology has revolutionized the services. Even though smartphones have spread well in the country, analog phones are equally valued as they enable customers and drivers to keep in touch through phone calls and short messages. Despite the significance of the technology, various challenges were observed, including poor digital skills and increasing road accidents.